Respon Pertumbuhan Bibit Kakao (Theobroma cacao L.) terhadap Pemberian Pupuk Kandang Ayam dan Pupuk Organik Cair - Liperi Tarigan; Ferry Ezra Sitepu; Ratna Rosanty Lahay (Jurnal Agroekoteknologi, 2014)
One of the factors that determine the quality of cocoa seedlings is fertility of growing medium.Fertility of growing medium can be increase with fertilization. For that purpose by using of chickenmanure and liquid organic fertilizer be expected to increase cocoa seedlings. This research wasconducted in experimental field of Agriculture Faculty University of North Sumatera in June 2013-September 2013 using randomize complete block design with two factors. The first factor is dose ofchicken manure (0,150 and 300 g/polibag) and the second factor is dose of liquid organic fertilizer(0,15,30, and 45 cc/L of water). Parameters observed were plant height, number of leaves, stemdiameter,total leaves area, fresh weight of shoot, fresh weight of root, dry weight of shoot, dryweight of root and ratio of dry weight of shoot/dry weight of root. From the research, chikenmanure significantly affect on plant height (12 and 14 WAP), number of leaves( 8-12 WAP), stemdiameter, total leaves area, fresh weight of canopy, dry weight of canopy and fresh weight of root.Liquid organic fertilizer unsignificantly affect on all parameters. Interaction of chiken manure andliquid organic fertilizer unsignificantly affect on all parameters. The best result from thisexperimental were obtained in the treatment of chicken manure at 300 g/polybag and liquid organicfertilizer 15 cc /L of water .